The Legal Review of Sexual Violence in Husband and Wife Relationships from the Perspective of Qiraah Mubadalah - Nandiya, Tanty Ayu; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The cycle of suffering. According to validated data from the Ministry of Women’s Empowerment and Child Protection (PPPA) in 2023, a total of 27,312 cases of alleged violence were reported, with 23,965 of the victims being women. Domestic violence committed by spouses is among the most common cases, with 20.2% of the victims being housewives. In light of this, the researcher conducted a study to examine the meaning of sexual violence within the context of law and Islamic teachings, particularly in Islamic households, with the aim of finding a balance of rights and obligations between husband and wife from the perspective of Qirah Mubjadi. The research method employed is a literature study. The results show that from the perspective of Qirah Mubjadi, sexual violence in marital relationships can be addressed through the principles of mutuality, mutual understanding, and reciprocal respect between husband and wife. Keywords: Sexual Violence, Islamic Law, Qira'ah Mubjadi, Rights And Obligations Of Husband And Wife, Literature Study